CRIME SCENE AS A CONSTITUENT ELEMENT OF OFFENCE IN THE SPHERE OF COMPUTER INFORMATION - A. I. Khaliullin (Russian Journal of Economics and Law)
The article views the problems of defining the crime scene of computer crimes in the interconnection of the state jurisdiction, as well as the normative-legal base of the states concerning the crimes of such type. Their characteristic features are described, the existing approaches to the issue of crime scene of computer-related crimes are analyzed.